2020
DOI: 10.3389/fpsyg.2020.599925
|View full text |Cite
|
Sign up to set email alerts
|

Written Emotional Disclosure Can Promote Athletes’ Mental Health and Performance Readiness During the COVID-19 Pandemic

Abstract: The widespread effects of the coronavirus disease 2019 (COVID-19) pandemic have negatively impacted upon many athletes’ mental health and increased reports of depression as well as symptoms of anxiety. Disruptions to training and competition schedules can induce athletes’ emotional distress, while concomitant government-imposed restrictions (e.g., social isolation, quarantines) reduce the availability of athletes’ social and emotional support. Written Emotional Disclosure (WED) has been used extensively in a v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
16
2
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(23 citation statements)
references
References 147 publications
0
16
2
2
Order By: Relevance
“…According to the results of statistical analysis, it is seen that the health literacy average scale scores of the athletes participating in the study are quite high, while coronavirus anxiety is low. Contrary to our study, in studies in which the anxiety levels of elite athletes were measured in the literature, it was found that the anxiety levels of elite athletes were high [35,36,37]. Many elite athletes spend this period in the home environment uncertainly, they have to train on their own and without supervision, the dates of the competition are not clear, these situations make this process difficult for the athletes [35,36].…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…According to the results of statistical analysis, it is seen that the health literacy average scale scores of the athletes participating in the study are quite high, while coronavirus anxiety is low. Contrary to our study, in studies in which the anxiety levels of elite athletes were measured in the literature, it was found that the anxiety levels of elite athletes were high [35,36,37]. Many elite athletes spend this period in the home environment uncertainly, they have to train on their own and without supervision, the dates of the competition are not clear, these situations make this process difficult for the athletes [35,36].…”
Section: Discussioncontrasting
confidence: 99%
“…Contrary to our study, in studies in which the anxiety levels of elite athletes were measured in the literature, it was found that the anxiety levels of elite athletes were high [35,36,37]. Many elite athletes spend this period in the home environment uncertainly, they have to train on their own and without supervision, the dates of the competition are not clear, these situations make this process difficult for the athletes [35,36]. Hull et al [37] state that the sudden cancellation and postponement of international competitions (Tokyo Olympics, etc.)…”
Section: Discussioncontrasting
confidence: 99%
“…Athletes travel frequently, so probably they also will need telehealth assistance after the COVID-19 situation has eased [ 24 ]. One suggested self-help technique to promote emotional processing and reduce emotional distress is the emotional expression protocol of Written Emotional Disclosure [ 25 ], wich helps to evaluate daily routines, maintain athletes’ mental health, and support their return to competition [ 26 ].…”
Section: Discussionmentioning
confidence: 99%
“…Also, within the general population, for which athletes make up a proportion, increased levels of domestic abuse, violence and mental health distress, including suicide rates, have been reported throughout the pandemic ( Schinke et al, 2020 ). However, athletes may have experienced specific challenges unique to their cohort too, such as various forms of mental health distress ( Davis et al, 2020 ; FIFPRO, 2020 ; Hull et al, 2020 ) and the pressure of public expectations ( Foskett and Longstaff, 2018 ) to be national and international ‘leaders’ in promoting healthy coping strategies throughout the pandemic. They may have felt obliged to take part in various sport challenges, as well as to communicate public health messages to their, typically large, fan-base, using their online social media platforms, for example ( Sharpe et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%